Water balance for different field capacities and rainfall erosive variability in the municipality of Amparo de São Francisco - SE, Brazil (Research, Society and Development, 2020)
The objective is to evaluate the water conditions through the climatic panorama of the variability of the field capacity aiming to detect the erosive fluctuations of the soil, in the municipality of Amparo de São Francisco - Sergipe by computing the water balance. Data on average monthly and annual rainfall were acquired from the database of the Northeast Development Superintendence and the Technical Assistance and Rural Extension Company of the state of Sergipe, between the years 1963 to 2019. The average temperature data were estimated by Estima_T software for the same study period. The methodology applied for computing the water balance was by Thornthwaite. Field capacity of 25 mm; 50 mm and 75 mm recorded high erosion rates. Field capacity of 100 mm; 125 mm and 150 mm showed moderate erosivity, and weak erosive indices for the 175 mm capacity. The rainfall rates for the studied field capacities are expected to cause more erosive incidences since heavy rains with great magnitudes and in a short period of time are expected. The results obtained indicate critical situations of the soil conditions of the studied area, which may cause great impacts on water resources and the practice of rainfed crops.